2023
DOI: 10.1111/psyp.14280
|View full text |Cite
|
Sign up to set email alerts
|

Facemasks selectively impair the recognition of facial expressions that stimulate empathy: An ERP study

Abstract: Previous research suggests that masks disrupt expression recognition, but the neurophysiological implications of this phenomenon are poorly understood. In this study, 26 participants underwent EEG/ERP recording during the recognition of six masked/unmasked facial expressions. An emotion/word congruence paradigm was used. Face‐specific N170 was significantly larger to masked than unmasked faces. The N400 component was larger for incongruent faces, but differences were more substantial for positive emotions (esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
2
3
0
Order By: Relevance
“…These findings indicate that the right OFA and the right FFA, independently, respond more strongly to masked neutral faces than to unmasked neutral faces, pointing to the need for more neural resources to correctly categorize and interpret these stimuli. Similarly, previous EEG studies showed larger N170 during the emotion recognition of masked (vs. unmasked) faces, suggesting that the processing of faces with surgical-like masks might require an amplified attentional process (Prete et al, 2022;Żochowska et al, 2022;Proverbio et al, 2023). One might hypothesize that the higher activations of the two ventral occipito-temporal regions support, in a compensatory manner, a feature-based processing of the face in order to identify its underlying expression on the basis of the configuration of the eyes and the forehead.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These findings indicate that the right OFA and the right FFA, independently, respond more strongly to masked neutral faces than to unmasked neutral faces, pointing to the need for more neural resources to correctly categorize and interpret these stimuli. Similarly, previous EEG studies showed larger N170 during the emotion recognition of masked (vs. unmasked) faces, suggesting that the processing of faces with surgical-like masks might require an amplified attentional process (Prete et al, 2022;Żochowska et al, 2022;Proverbio et al, 2023). One might hypothesize that the higher activations of the two ventral occipito-temporal regions support, in a compensatory manner, a feature-based processing of the face in order to identify its underlying expression on the basis of the configuration of the eyes and the forehead.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown that masking heavily affected emotion recognition, reducing the recognizability of facial expressions (Proverbio and Cerri, 2022;Rinck et al, 2022) and emotion recognition accuracy (Carbon, 2020;Ruba and Pollak, 2020;Calbi et al, 2021;Grundmann et al, 2021;Marini et al, 2021). A previous EEG study investigated the cerebral activity related to the recognition of six masked/unmasked facial expressions by using event-related potentials (ERPs) analyses (Żochowska et al, 2022;Proverbio et al, 2023). The results indicated increased neuronal activity during facemasked emotion recognition.…”
Section: Introductionmentioning
confidence: 99%
“…However, these effects widely varied on the emotional expressions. First, reactions to angry expressions remained unaffected, aligning with evidence indicating that surgical masks did not hinder the recognition of angry faces (Grahlow et al, 2022;Proverbio and Cerri, 2022;Rinck et al, 2022;Gil and Le Bigot, 2023;Proverbio et al, 2023). Second, fearful masked faces increased the RTs with respect to unmasked stimuli, while they had no impact on MTs and OERs.…”
Section: The Impact Of the Surgical Mask On Behavioral Reactions To E...supporting
confidence: 75%
“…Last but not least, one should keep in mind that the 2-back task is a classical paradigm of working memory that involves attention and executive components but not emotional processing. This latter seems to be the most vulnerable domain of human cognition when wearing a facemask ( Ferrari et al, 2021 ; Grundmann et al, 2021 ; Marini et al, 2021 , 2022 ; Proverbio and Cerri, 2022 ; Tsantani et al, 2022 ; Proverbio et al, 2023 ). Future fMRI studies including tasks of social cognition are warranted to explore whether the wearing of facemask modifies brain activation patterns when dealing with emotional processing in complex environments.…”
Section: Discussionmentioning
confidence: 99%
“…However, some lines of evidence indicated that facemasks may alter concentration and visual attention in maximal running aerobic tests ( Slimani et al, 2021 ). By impacting social interaction, facemasks modify the neural responses to recognition of facial cues but also pivotal human abilities serving our daily behavior such as emotion recognition that stimulate empathic responses, perceived closeness, trust attribution and even re-identification of unmasked faces ( Ferrari et al, 2021 ; Grundmann et al, 2021 ; Marini et al, 2021 , 2022 ; Proverbio and Cerri, 2022 ; Tsantani et al, 2022 ; Proverbio et al, 2023 ). In contrast to behavioral changes, data on the effect of wearing a facemask on brain activation remain rare.…”
Section: Introductionmentioning
confidence: 99%